Is maternal cigarette or water pipe use associated with stopping breastfeeding? Evidence from the Jordan population and family health surveys 2012 and 2017-18 - Esra Can Özalp; S. Songül Yalçın (BMC, 2021)
Abstract Background Maternal smoking is suspected to have negative impacts on breastfeeding, such as decreasing the quantity of breast milk, and reducing vitamin and fat concentrations in the milk in the late lactation period. Cigarette and water pipe tobacco products are widely used in Jordan. We aimed to estimate the association between use of different tobacco products and the rates of current breastfeeding. Methods Data from Jordan's Population and Family Health Surveys 2012 and 2017-18 were examined. Last-born, living children, aged < 25 months, from singleton births, ever breastfed, and living with their mother were included. The key outcome variables were the current breastfeeding (during last 24 h) and tobacco usage status [water pipe tobacco (hookah or narghile) and/or cigarette tobacco]. Complex sample multivariate logistic regression analysis was used to evaluate the association of the current breastfeeding with maternal smoking status. Results Overall, 6726 infants were included in the study. The current breastfeeding rate in infants aged 0-6 months was 87%, compared with 43.9% in infants aged 12-17 months and 19.4% in infants aged 18-24 months. Overall, 4.4% had mothers who smoked cigarettes, 5.4% smoked water pipe, and 1.6% both cigarettes and water pipe. The proportion of breastfed infants in non-smoking mothers was 57.7% and, those in smoke water pipe, cigarette and both tobacco products were 55.4, 44.9, and 51.0% respectively. Univariate analysis revealed that women cigarette smokers had a lower odds ratio (OR) for current breastfeeding (OR 0.60, 95% Confidence Interval [CI] 0.39, 0.92). Multivariate analysis revealed that maternal cigarette smoking was associated with a lower odds ratio for current breastfeeding compared with mothers who smoked neither water pipe nor cigarettes (AOR 0.51, 95% Cl 0.30, 0.87). Conclusions These results indicate that maternal smoking is associated with termination of breastfeeding, suggesting that structured training should be organized for healthcare professionals, expectant mothers and the general public about the association between maternal smoking and cessation of lactation.